Improving phenylalanine and micronutrients status of children with phenylketonuria: a pilot randomized study - Reza Zamani (BMC, 2021)
Abstract Background Children with Phenylketonuria (PKU) need a special diet to avoid a variety of physical and psychological complications. The aim of this study was to compare and assess the effects of two interventions on and levels of phenylalanine and micronutrients in children with PKU. Methods Forty-six children with PKU (ages 1–12 years) and their caregivers were randomly assigned to one of two 10-week interventions: a caregiver educational intervention based on the Integrative Model of Behvioral Prediction (IMBP) and supplementary low-protein-modified foods. Outcomes consisted of Children's plasma phenylalanine and micronutrients (i.e., vitamin B12, vitamin D3, and zinc) and hemoglobin levels. To assess the sustainability of outcomes, we also compared the children’s phenylalanine level at five-time points including baseline and 10-week, 6 months, 12 months, and 24 months follow-ups. In addition, caregivers of both groups were asked to complete a questionnaire to assess how well the interventions were implemented as well as satisfaction with interventions. Results While a large percentage of children had phenylalanine levels out of range indicating non-adherence (69.6% and 81% in the educational and food items group, respectively), micronutrient deficiencies were not prevalent in the patient cohort. The levels of phenylalanine in both groups decreased significantly over time. However, conducting a repeated-measures ANOVA to evaluating the change in groups across five-time points, revealed a significant difference between groups (F = 4.68, p = 0.03). That is, the educational intervention was more effective in lowering the children's phenylalanine level. At 24-month follow-up, the percentage of children with a normal range of phenylalanine level in the educational and food items groups increased to 73.9 and 57.1 percent, respectively, from 26 and 38 percent at baseline. There were no significant changes in children's micronutrients level following the interventions, except in the hemoglobin. In this way, at 10-week follow-up, the mean hemoglobin of children in the educational group reduced significantly (P = 0.041). However, there was no significant difference between the two groups. In general, all caregivers completed the process evaluation checklist, the feedback was largely positive. Conclusions The results of this study demonstrated that both educational and providing food item interventions resulted in a significant reduction in phenylalanine levels. Empowering caregivers of patients, creating and fortifying social networks, providing favorable social supports, and providing access to special food items may be effective in controlling PKU. Clinical trial registration: Iranian Registry of Clinical Trials (IRCT20180506039548N1). Registered 6th Jun 2018, https://www.irct.ir/trial/30977 .